The Dietary Pattern and Hemoglobin Status of School-Age Children in Odeda Local Government Area of Ogun State in Nigeria - Jumoke Georgina Ilo; Oluseye Olusegun Onabanjo; Catherine Olubukola Badejo; Olajide P. Sobukola (Food, Agriculture and Natural Resources - NETWORKS, 2022)
Iron deficiency is the most common case of micronutrient deficiency in the world and widely known to cause anemia. School-age children are at high risk of micronutrient deficiency due to increased energy expenditure, combined with decreased meal frequency and insufficient maternal attention as well as parasitic infections. This study assessed the dietary pattern and hemoglobin status of school-age children in Odeda Local Government area of Ogun State in Nigeria. Two-hundred-and-twenty-seven (227) children from two schools were recruited for the study. Data on the socio-demographic characteristics of the respondents and consumption pattern were obtained through a semi-structured questionnaire. Anthropometric measurements (height and weight) of the children were determined using standard anthropometric procedures, while anthropometric indices were measured against WHO growth standard. Blood samples of the subjects were collected and analysed for haematological variables (haemoglobin, serum transferrin, and serum ferritin). Data were analyzed using frequency count, percentage, and mean. Research results have revealed that regular consumption of fruits is generally low (6.8%) among respondents. Most of the respondents (61.0%) consume green leafy vegetables on a regular basis, while 54.3% and 46.3% consume meat and fish more than 4 times per week, respectively. The anthropometric measurement of the subjects at baseline shows that 17.2% are severely stunted (HAZ-3SD), 19.5% are moderately stunted (-3SD<HAZ<-1SD), and 39.4% are mildly stunted (‐2 SD < HAZ <‐1 SD). The BAZ status record that 14.1% are underweight (BAZ<-2SD), 1.4% are overweight (2 SD > BAZ >1 SD), and 0.8% are identified with obesity (BAZ >2 SD). Biochemical status shows that 54.9% are anemic, while all (100.0%) of the children have adequate ferritin and transferrin status. This study has acknowledged that school-age children in Odeda local government face serious prevalence of anemia associated with causes beyond the lack of iron-rich food sources.